Republic of Mozambique : Diagnostic Report on Transparency, Governance and Corruption. (IMF Staff Country Reports; Country Report, 2019)
This Diagnostic Report on Transparency, Governance and Corruption for the Republic of Mozambique highlights that the economy is at a turning point, and efforts to address governance and corruption vulnerabilities can have a lasting positive impact. The current levels of public debt have caused us to take a hard look at our governance and anticorruption framework and have prompted various reforms to address the vulnerabilities exposed in this framework. The governance and anticorruption framework is not consistently or comprehensively enforced. The rule of law is undermined by the insufficient implementation of existing legislation and regulations, including, in some cases through the absence of necessary regulations and explanatory guidelines. Civil society, the private sector, and the development partners in Mozambique also have critical roles to play. In addition, issues related to poor governance and corruption cannot be effectively addressed unless similar attention is paid to their transnational aspects, which need to be handled at a regional and global level, in multilateral and other international fora.